Compliance assessment of cigarette and other tobacco products act in public places of Alwar district of Rajasthan - M L Jain; Mamta Chauhan; Rajani Singh (Wolters Kluwer Medknow Publications, 2016)
Background: The Government of India has taken various initiatives for tobacco control by enacting comprehensive tobacco control legislation (Cigarette and Other Tobacco Products Act [COTPA], 2003). Objectives: The aim of this study was to assess the level of compliance of Sections 4, 5, 6-a, and 6-b, and 7, 8, and 9 of COTPA with respect to public places, educational institutes, point of sale (PoS), and warning on packaging (COTPA) in public places of Alwar District of Rajasthan. Methods: A cross-sectional observational study was conducted in 2014 in Alwar city and four blocks of the district. The study was done around 365 public places for observing the compliance of Section 4 of COTPA, 357 educational institutions for observing the compliance of Section 6-b of COTPA, and 357 tobacco retailers for observing the compliance of Sections 5 and 6-a of COTPA. Results: The criteria for the evaluation (the core indicators) and decision criteria for a district to qualify for the "Smoke free" status include six parameters. From the total of 365 places visited, 90% places displayed the "No-smoking" signage and out of total 328 places, 99% were as per the COTPA specification. Alwar city, Ramgarh, Thanagaji, and Alwar rural block followed the compliance of Section 4. The PoS visited Alwar district displayed 93% (332) signage and all the displayed signage followed the COTPA compliance. In Alwar city, Thanagaji, Ramgarh, and Alwar rural block, the compliance of Section 6-a was above 90%. The compliance of Section 6-b was above 90% in Alwar city, Ramgarh, Thanagaji, and Alwar rural block. Ninety-three percent (332) of the PoS did not display tobacco advertisement in Alwar district, which is a positive sign of COTPA compliance. Conclusion: This finding suggest a high level of compliance of Section 4, Section 5, Section 6-a, and Section 6-b of COTPA at Alwar district.